GUILT EFFECT TO CHARACTER’S HARUMA SELF-DEFENSE MECHANISM - Dinata, Yuda Prawira; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This journal seeks to find out how guilt affects the self-defense mechanisms of the character Haruma in the manga Inu to Kuzu. The method used is descriptive qualitative to find out the influence of guilt on Haruma using findings from pictures and dialogue. Based on research findings, it was found that Haruma’s character experienced a self-defense mechanism of repression, which made him forget memories of events that made him feel guilty